2006
DOI: 10.1055/s-2006-925160
|View full text |Cite
|
Sign up to set email alerts
|

Controversy Concerning the Cutoff Value for Depth of Submucosal Invasion after Endoscopic Mucosal Resection of Early Gastric Cancer

Abstract: We read with interest the recent article by the Endoscopic Classification Review Group [1]. Endoscopic mucosal resection (EMR) has become widely accepted as a curative treatment for mucosal cancer of the stomach [2], and recent advances in EMR techniques are extremely remark− able. A new endoscopic procedure, using multiple accessories, provides an en bloc specimen and therefore allows precise histologic staging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…This also comes from a concept of investigating the nature of gut as a full layer rather than a partial one after artificial stretching. Furthermore, simple one-step stretching attempted in the previously cited report 7 would not prove any correlation of the extent of stretching and subsequent thinning of submucosal layer.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…This also comes from a concept of investigating the nature of gut as a full layer rather than a partial one after artificial stretching. Furthermore, simple one-step stretching attempted in the previously cited report 7 would not prove any correlation of the extent of stretching and subsequent thinning of submucosal layer.…”
Section: Introductionmentioning
confidence: 73%
“…Thickness of tissue may vary depending on the manual force given for stretching before tissue fixation, and not the whole layer but partial layer including mucosa and superficial submucosa are taken after EMR. 7 In our view, submucosal thickness still has reason to be evaluated as a component of intact thickness, although the tissue retrieved after EMR is partial rather than a full layer of gut. This premise originates from an idea to validate the previously suggested cut-off value of 500 um by the ECRG.…”
Section: Introductionmentioning
confidence: 97%
“…A final limitation is particularly relevant to submucosal cancers regarding the measurement of depth of invasion. Some studies have reported that depth of invasion might be influenced by the amount of desmoplasia and could decrease as the specimen is stretched29, 30. Song and colleagues31 found microscopic margins that were negative after EMR or ESD, but scattered residual cancer cells near the EMR or ESD site after surgery, in two of ten patients with submucosal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The accuracy of preoperative diagnosis of nodal metastases in EGC using computed tomography varies widely by methodology [29,30]. In this study, the accuracy of preoperative diagnosis was relatively low, and we did not know whether nodal metastases were present until we performed surgery with lymphadenectomy.…”
Section: Discussionmentioning
confidence: 89%